California County Planning Commissioners Association Conference-Lake Tahoe - Watkins, Howard::::::::: (1983)
Jack Lish (Placer) introducing "Biomass Energy Systems-a New Planning Issue" Panelists: Joe Hunter, Robert Lancaster, Paul Chesney, and Don Demars